Breast shells for pain and nipple injury prevention: A non-randomized clinical trial - Jessica Oliveira Cecilio; Flaviana Vely MendonçaVieira; Flávia Silva Oliveira; Janaína Valadares Guimarães; Natalia Del'Angelo Aredes; Danielle Rosa Evangelista; Suzanne Hetzel Campbell (PEC Innovation, 2022)
Objective: This study aimed to analyze the effectiveness of breast shells in preventing pain and nipple injury during breastfeeding. Method: A non-randomized clinical trial was carried out with blinding to the evaluators of the study results. The study included women with ≥35 weeks of singleton pregnancy, no nipple changes, and a desire to breastfeed. Resulting in 62 lactating women. The experimental group used breast shells and health education with clinical demonstration (n = 29), whereas the control group used no breast shells (n = 33). Pain and nipple injury were assessed three times, twice prenatally and once up to 14 days postpartum. Results: Nipple injury (50.0%) and nipple pain (67.7%) presented with similar frequency in both groups (p = 1). Breast engorgement (35,5%) was associated with nipple pain (p = 0.019) and its onset was delayed in the experimental group (p = 0.001). Health education contributes to breast and nipple care and increases favorable breastfeeding patterns. Conclusion: Breast shells do not prevent nipple pain or injury. Innovation: As far as we know, this is the first clinical research evaluating the use of breast shells since the antenatal care to prevent the occurrence of nipple pain and injury.